1982
DOI: 10.1016/0377-0273(82)90028-2
|View full text |Cite
|
Sign up to set email alerts
|

Geological, geophysical, and thermal characteristics of the Salton Sea Geothermal Field, California

Abstract: This is a preprint of I paper intended for publication in a Journal or proceedlnEs. Since channes mav be made before Dubliatbn. thb DreDrint is made avrilable with the un--. . dentmndhg that it will not be cited or reproduced without the prmisaion of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…Instead, enhancement of the heat propagation by the fluid circulations would be efficient enough to reach gradients of more than 100 • C km −1 . Similar gradients are reported in the Salton Sea (Muffler and White, 1969;McDowell and Elders, 1980;McDowell and Elders, 1983), where Younker et al (1982) identified small-scale convection cells beneath an impermeable cap rock.…”
Section: Estimating the Importance Of Fluid Circulationssupporting
confidence: 81%
“…Instead, enhancement of the heat propagation by the fluid circulations would be efficient enough to reach gradients of more than 100 • C km −1 . Similar gradients are reported in the Salton Sea (Muffler and White, 1969;McDowell and Elders, 1980;McDowell and Elders, 1983), where Younker et al (1982) identified small-scale convection cells beneath an impermeable cap rock.…”
Section: Estimating the Importance Of Fluid Circulationssupporting
confidence: 81%
“…[5] The ammonia sources described in the present work were discovered during the course of an airborne hyperspectral longwave infrared (LWIR, 8-13 mm) imaging survey of the Salton Sea Geothermal Field (SSGF), an area of significant geothermal activity in southern California [Younker et al, 1982]. Within the SSGF, the presumed surface track of the Calipatria Fault contains numerous fumaroles and other hydrothermal features much in evidence, some of which have been previously described [Svensen et al, 2007;Lynch and Hudnut, 2008;Rudolph and Manga, 2010;Onderdonk et al, 2011].…”
Section: Field Experimentsmentioning
confidence: 85%
“…Fry analysis can indicate the direction of tectonic stress by locating spots and points and calculating their direction distribution, thus indicating the distribution direction of point or line objects. Later, many scholars expanded the scene of application to spatial distribution analysis [39,40] and achieved good results [6]. Fry analysis [41] can operate manually by using a sheet of tracing paper on which a series of parallel reference lines (typically north pointing on a map) have been drawn and the location of each data point is recorded.…”
Section: Hot Spring Data Processing By the Fry Methodsmentioning
confidence: 99%